Comparação entre pediculectomia e hemilaminectomia no tratamento da extrusão de disco intervertebral toracolombar em cães. Estudo retrospectivo - Penteado, Bianca Mota (2011)
The thoracolumbar intervertebral disk extrusion in dogs causes compression of the spinal cord and can pinch the nerve roots. The choice of medical or surgical treatment remains controversial, although there is general agreement that some form of decompressive surgery is indicated for those patients with moderate to severe neurological dysfunction. We retrospectively studied the results of pediculectomia (P) and hemilaminectomy (H) as a treatment in ETL in 76 dogs, grouped according to race, gender, body mass, age and neurological status, duration of clinical signs, involvement of the intervertebral discs, time recovery time and success rate of surgery. The dachshund was the most represented (n = 42). Males comprised 52.7% (n = 39), the mean age was 4.6 years and the weight ranged from 3.2 to 22 kg. Nineteen animals were classified neurologically as grade II (GII) - ambulatory paresis (P = 9, H = 10), 26 as grade III (GIII) - Non-ambulatory paresis (P = 14, H = 12) and 31 dogs as grade IV (GIV) - paraplegia (P = 14, H = 17). The average duration of clinical signs was 24.1 days (GII), 18.6 days (GIII) and 12.7 days (GIV). The most affected were DIV T10/11 (6.6%), T11/12 (13.2%), T12/13 (25%), T13/L1 (35.5%), L1 / 2 (11.8 %) and L2 / 3 (7.9%). The average recovery time for GII-P was 5.6 days and 6.1 for H-GII, GIII 19.2 days to 22.4 days, P and G to H-III, and 27.5 days (GIV -P) and 33.6 (GIV-H), and success rate was respectively 100 and 89.9% for GII and GII-P-H, 100 and 83.4% for GIII GIII and-P-H and 92.9 and 76.4% for GIV and GIV-P-H. Surgical time was 80.7 ± 12.4 minutes for P and 86.8 ± 19.8 minutes for H. It was concluded that the pediculectomia is alternative to hemilaminectomy, showing slight superiority in the results probably due to better access to the extruded disc material.